Scientific visualization of BioHeat process/ Rosnani Ramin - Rosnani, Ramen (2005)
Development in visualization technology is changing the way science is undertaken in many areas of research. This project is a system specifically designed to manage and visualize the temperature data of the human body. Knowledge in certain domains is very important in developing the visualization of bioheat process system. There are two main areas of research needed to carry out in order to marks the whole project succeed, research on the visualization program tools and research on the bioheat process in the human body. As the result of research, MATLAB was chosen to be the core-programming tool. An important aspect of this system is to visualize temperature bio heat process of heat transfer. The objective of this system is to illustrate how programming, modeling and simulation of a transient PDE problem using a mathematical software package in MATLAB. There are two major categories of user had been determined, which can be categorized into expert and non-expert user. The user will benefit from this system as it is visualization and it is repository that is rich in various artificial intelligent and multimedia contents.